PENGEMBANGAN MEDIA AUDIO VISUAL UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN PENDIDIKAN PANCASILA MENGGUNAKAN APLIKASI CAPCUT - Subhan, Muhammad; Darniyanti, Yulia; Sandia, Eci`` (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2025)
This study aims to develop a learning media to raise students' enthusiasm in the learning process or when evaluating learning on the Pancasila Education learning content. Therefore, researchers are interested in developing an interesting learning media that can make students interested in following the learning process. Which media uses audio-visual media (animated videos). The problem is that students feel bored in the learning process. The type of development research (R & D), while the model used is the ADDIE model has steps including Analysis, Design, Development, Implementation and Evaluation. The types of data used are qualitative data and quantitative data. The development of the instrument used is an analysis instrument for students, practicality, effectiveness. Data collection techniques use teacher and student response questionnaires, interviews, observations and documentation. Data analysis techniques use validity, practicality and effectiveness analysis techniques. Based on the development that has been carried out with audio-visual media in Pancasila Education learning for class IV SDN 06 Koto Baru. It can be concluded as follows: 1) Validation of audio-visual learning media in learning Pacasila Education class IV SDN 06 Koto Baru was assessed by three validators. With an average validation value of 85% with a very valid category. 2) Practicality assessed by the homeroom teacher and 16 students on animated video learning media obtained an average of 96.86% with a very practical category. 3) Effectiveness assessed from student learning outcomes obtained an average of 87.5% with a very effective category. By using this media, student learning outcomes are better than before.